Mystical, Ontological, and Functionalist According to Cornelis Anthonie Van Peursen in The Theory of Philosophy of Science - Ahmad Qomarudin; Maslahah Maslahah; Arina Zulva Maulida (Yayasan Literasi Sains Indonesia, 2022)
The world of philosophy has many approaches to obtaining the truth from a symptom that arises around humans. These approaches include both scientific and non-scientific approaches. Of these approaches, there are positivistic approaches and non-positivistic approaches. There is a lot of debate between these two schools, one of the characters is Cornelis Anthonie van Peursen who often criticizes the positivistic with his mindset so that he is called a non-positivistic figure and alludes also to the problem of cultural strategy that he initiated. The purpose of writing this scientific article is to understand in more detail the philosophy and how Cornelis Anthonie van Peursen's critique of positivism and its cultural strategy concerning the mystical, ontological, and functionalist in search for truth. This research was conducted through a review of literature studies. The author examines various relevant sources obtained from books, journal articles, and supporting readings to enrich the content of this scientific article. Researchers used Miles and Huberman's model data collection techniques, including data reduction, data presentation, and drawing conclusions and verification. The results of the study stated that Van Peursen divided culture into three dimensions, namely mythic, ontological, and functionalist. The mystical stage is characterized by when a man believes that in his life he is surrounded by the forces that surround them. The ontological stage is characterized when a man has begun to use logic as a foothold for thinking, man has been freed from mythic power and dares to test things concretely. The functionalist stage is characterized by the attitude and state of mind that nature has not only been made an object but has become a tool to meet human needs to make life comfortable. This stage is characterized by the industrial revolution in the world and man treats nature by over-exploring it.